Oxygen coordination cobalt monatomic catalyst as well as preparation method and application thereof

CN119701955AActive Publication Date: 2025-03-28TSINGHUA UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411701216.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing synthesis method of oxygen-coordinated cobalt single-atom catalysts has problems such as cumbersome steps, single substrate, and limited regulatory space, making it difficult to provide high-performance catalysts. At the same time, the electrocatalytic system is insufficient in stability and reliability in the face of fluctuations in green power, making it difficult to effectively couple with the photovoltaic system.

Method used

Cobalt was introduced into a three-dimensional framework composed of terephthalic acid and zinc self-assembled. After carbonization, the Co–O–C coordination structure was retained to prepare an oxygen-coordinated cobalt single-atom catalyst. At the same time, a working condition simulation electrochemical test method was designed to evaluate the stability of the catalyst and the accumulated Faraday efficiency of the system.

Benefits of technology

The high-performance preparation of oxygen-coordinated cobalt single-atom catalyst is achieved, and the selectivity of the two-electron oxygen reduction reaction and the stability of the catalyst are improved. It is suitable for the application of electrocatalytic oxygen reduction in the preparation of hydrogen peroxide. At the same time, through simulated working condition testing methods, the flexibility and adaptability of the catalyst are evaluated, providing technical support for the coupling of green energy and electrocatalytic systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005153349910000011
    Figure HDA0005153349910000011
  • Figure HDA0005153349910000012
    Figure HDA0005153349910000012
  • Figure HDA0005153349910000021
    Figure HDA0005153349910000021
Patent Text Reader

Abstract

The invention provides an oxygen coordination cobalt monatomic catalyst, a preparation method and application thereof, the oxygen coordination cobalt monatomic catalyst is composed of a porous carbon skeleton, cobalt monatomic and oxygen atoms, the specific surface area of the porous carbon skeleton is 100-3000 m < 2 > / g, the mass content of the cobalt monatomic is 0.01%-10%, and the mass content of the oxygen atoms is 1%-15%. According to the catalyst, an oxygen-enriched metal organic framework is used for anchoring a cobalt metal center, and Co-O-C is formed after carbonization. In the oxygen coordination cobalt monatomic catalyst, an oxygen coordination structure can regulate an electronic structure of central metal cobalt to promote transfer of active sites and provide optimal intermediate * OOH adsorption energy, so that the selectivity of 2e-ORR is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to an oxygen-coordinated cobalt single-atom catalyst, a preparation method and application thereof. Background Art

[0002] Oxygen is an abundant natural resource that can be used to generate oxygen through electrocatalytic two-electron oxygen reduction (2e - Oxygen reduction reaction (ORR) can efficiently produce hydrogen peroxide (H2O2). H2O2 has wide applications as a green oxidant in many fields. Single-atom site carbon-based catalysts show great potential in the two-electron oxygen reduction reaction due to their high atom utilization and tunable structural properties.

[0003] Numerous studies have shown that by constructing Co-N x -C site can significantly improve the activity and selectivity of the catalyst (Angew. Chem. Int. Ed., 2020, 60, 4448–4463). Compared with nitrogen coordination, oxygen coordination can promote the transfer of active sites by adjusting the electronic structure of the central metal cobalt, providing the best intermediate adsorption energy, thereby improving the 2e - Selectivity of ORR (J.Am.Chem.Soc.,2021,143,7819–7827). At present, the synthesis methods of oxygen-coordinated cobalt single-atom catalysts mainly rely on traditional methods such as wet chemical impregnation or carbonization fixation, which have limitations such as cumbersome steps, single substrate, and limited regulation space (Energy Environ.Sci.,2024,17,1950–1960). Therefore, it is necessary to develop new synthesis strategies to overcome the shortcomings of existing technologies and provide high-performance catalysts.

[0004] With the pursuit of sustainable energy, electrocatalytic technology combined with green energy such as solar and wind energy provides an effective way to reduce carbon emissions and improve energy efficiency. However, the intermittent and variability of green energy poses a challenge to the stability and reliability of electrocatalytic systems. Electrocatalytic systems need to have a high degree of flexibility and adaptability to face the fluctuations of green electricity and achieve effective coupling with green energy such as photovoltaic systems. Based on non-steady-state power input, the testing and evaluation methods of catalysts / systems are a powerful means to promote the efficient use of green electricity, but related research is currently scarce. Summary of the invention

[0005] In view of the above-mentioned problems and limitations of the prior art, one of the objects of the present invention is to provide an oxygen-coordinated cobalt single-atom catalyst, in which cobalt is introduced into a three-dimensional framework self-assembled by terephthalic acid and zinc using a bottom-up synthesis method, and the Co–O–C coordination structure is retained after carbonization.

[0006] The second purpose of the present invention is to design an electrochemical test method for operating condition simulation to evaluate the performance of electrocatalytic oxygen reduction to prepare hydrogen peroxide. Start-stop and fluctuating operating conditions are simulated to evaluate catalyst stability, catalyst Faraday efficiency and the cumulative Faraday efficiency of the system.

[0007] In the first aspect of the present invention, the present invention provides an oxygen-coordinated cobalt single-atom catalyst. According to an embodiment of the present invention, the oxygen-coordinated cobalt single-atom catalyst is composed of a porous carbon skeleton, cobalt single atoms and oxygen atoms, and the specific surface area of ​​the porous carbon skeleton is 100 to 3000 m 2 / g, the mass content of the cobalt single atom is 0.01% to 10%, and the mass content of the oxygen atom is 1% to 15%. The catalyst uses an oxygen-rich metal organic framework to anchor the cobalt metal center and forms Co-O-C after carbonization. In this oxygen-coordinated cobalt single atom catalyst, the oxygen coordination structure can adjust the electronic structure of the central metal cobalt to promote the transfer of active sites, provide the best intermediate *OOH adsorption energy, and thus improve 2e - Selectivity of ORR.

[0008] In another aspect of the present invention, the present invention also proposes a method for preparing an oxygen-coordinated cobalt single-atom catalyst. According to an embodiment of the present invention, the method comprises:

[0009] 1) dissolving a cobalt salt and a zinc salt in an organic solution to obtain a solution A;

[0010] 2) dissolving terephthalic acid in an organic solution to obtain solution B;

[0011] 3) mixing the solution A, the solution B and triethylamine to obtain a metal organic framework material containing oxygen coordination;

[0012] 4) washing and drying the oxygen-coordinated metal organic framework material to obtain a precursor;

[0013] 5) subjecting the precursor to a carbonization reaction to obtain a powder catalyst;

[0014] 6) The powder catalyst is subjected to heating reflux treatment to obtain an oxygen-coordinated cobalt single-atom catalyst. Cobalt is introduced into a three-dimensional framework self-assembled by terephthalic acid and zinc using a bottom-up synthesis method, and the Co-O coordination structure is retained after carbonization.

[0015] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0016] According to an embodiment of the present invention, the organic solvent in step 1) and step 2) is the same.

[0017] According to an embodiment of the present invention, the organic solution is selected from one or more of N,N-dimethylformamide, water, ethanol and methanol.

[0018] According to an embodiment of the present invention, the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:(0.1-1):(0.01-0.5).

[0019] According to an embodiment of the present invention, the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:1:(0.01-0.1).

[0020] According to an embodiment of the present invention, the volume ratio of N,N-dimethylformamide, water and ethanol is (1:0.05)-(0.1:0.05)-0.1.

[0021] According to an embodiment of the present invention, the cobalt salt and the zinc salt are respectively one or both of nitrates and chlorides.

[0022] According to an embodiment of the present invention, the mixing process is performed by ultrasonic aging.

[0023] According to an embodiment of the present invention, the ultrasonic aging time is 1 to 10 hours.

[0024] According to an embodiment of the present invention, the temperature of the ultrasonic aging is 20-45°C.

[0025] According to an embodiment of the present invention, the temperature of the drying process is not less than 70°C.

[0026] According to an embodiment of the present invention, the drying process is performed under a vacuum environment.

[0027] According to an embodiment of the present invention, the drying process takes 8 to 12 hours.

[0028] According to an embodiment of the present invention, the carbonization process is performed under an argon atmosphere.

[0029] According to an embodiment of the present invention, the heating rate of the carbonization treatment is 2-5° C. / min.

[0030] According to an embodiment of the present invention, the temperature of the carbonization treatment is 800-1000°C.

[0031] According to an embodiment of the present invention, the carbonization treatment time is 1 to 5 hours.

[0032] According to an embodiment of the present invention, the carbonization treatment time is 3 hours.

[0033] According to an embodiment of the present invention, the heating reflux treatment is performed in an acidic solution.

[0034] According to an embodiment of the present invention, the concentration of the acidic solution is 0.1-3 mol / L.

[0035] According to an embodiment of the present invention, the concentration of the acidic solution is 1 mol / L.

[0036] According to an embodiment of the present invention, the temperature of the heating reflux treatment is 40-100°C.

[0037] According to an embodiment of the present invention, the temperature of the heating reflux treatment is 60-80°C.

[0038] According to an embodiment of the present invention, the heating reflux treatment time is 2 to 24 hours.

[0039] In another aspect of the present invention, the present invention provides a method for preparing an oxygen-coordinated cobalt single-atom catalyst. According to an embodiment of the present invention, the method comprises the following steps:

[0040] (1) dissolving a cobalt salt and a zinc salt in an organic solution to obtain solution A, and dissolving terephthalic acid in the same organic solution to obtain solution B;

[0041] (2) mixing the clear solution A obtained in step (1) with the solution B, adding triethylamine dropwise thereto, uniformly dispersing the solution through ultrasonic aging, and centrifuging to separate the oxygen-coordinated metal organic framework material;

[0042] (3) washing and drying the metal organic framework material of step (2) to obtain a precursor;

[0043] (4) carbonizing the precursor of step (3) at high temperature under the protection of an inert atmosphere to remove zinc and obtain a powder catalyst;

[0044] (5) The powder catalyst of step (4) is heated and refluxed in an acidic solution to remove excess cobalt particles, thereby finally obtaining an oxygen-coordinated cobalt single atom catalyst.

[0045] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0046] According to an embodiment of the present invention, the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:1:(0.01-0.1).

[0047] According to an embodiment of the present invention, the organic solution components include one or more of N,N-dimethylformamide, water, and ethanol.

[0048] According to an embodiment of the present invention, the volume ratio of N,N-dimethylformamide, water and ethanol is (1:0.05)-(0.1:0.05)-0.1.

[0049] According to an embodiment of the present invention, triethylamine is added dropwise to coordinate the metal with oxygen in terephthalic acid to form a metal organic framework carrier, and the ultrasonic aging time is 5 to 10 hours, and the liquid temperature is maintained at 20 to 35°C.

[0050] According to an embodiment of the present invention, the high temperature carbonization heating rate is 2-5° C. / min, the temperature range is 800-950° C., and the carbonization time range is 3 hours.

[0051] According to an embodiment of the present invention, the concentration of the acidic solution is 1 mol / L.

[0052] According to an embodiment of the present invention, the heating reflux temperature is controlled at 60-80° C., and the reflux time is 2-12 hours.

[0053] In another aspect of the present invention, the present invention proposes the use of the oxygen-coordinated cobalt single-atom catalyst described above or the oxygen-coordinated cobalt single-atom catalyst prepared according to the method described above in the electrocatalytic reduction of oxygen to prepare hydrogen peroxide.

[0054] According to an embodiment of the present invention, the above application may further include at least one of the following additional technical features:

[0055] According to an embodiment of the present invention, the electrocatalytic oxygen reduction to prepare hydrogen peroxide is carried out in an acidic medium.

[0056] According to an embodiment of the present invention, the acidic medium is one of perchloric acid, sulfuric acid or hydrochloric acid.

[0057] According to an embodiment of the present invention, the concentration of the acidic medium is 0.01-1 mol / L.

[0058] According to an embodiment of the present invention, the concentration of the acidic medium is 0.1 mol / L.

[0059] According to an embodiment of the present invention, the acidic medium is 0.1 mol / L perchloric acid.

[0060] According to an embodiment of the present invention, the electrocatalytic oxygen reduction to prepare hydrogen peroxide is carried out in a flow electrolysis cell.

[0061] According to an embodiment of the present invention, the flow electrolysis cell utilizes one of constant current electrolysis, constant voltage electrolysis or new energy simulated working condition electrolysis.

[0062] According to an embodiment of the present invention, the simulated operating condition in the application is one or more of start-stop and fluctuation operating conditions.

[0063] According to an embodiment of the present invention, the current density in the simulated working condition is 10-500 mA / cm 2The start-stop interval is 0.01 to 20 h / time; the fluctuating operating condition is to perform alternating electrolysis at 5 to 20% and 120 to 150% of the rated current density, and the fluctuation frequency is 0.01 to 20 h / time.

[0064] In another aspect of the present invention, the present invention also proposes a test for preparing hydrogen peroxide by electrocatalytic oxygen reduction. According to an embodiment of the present invention, the test includes using carbon paper as a gas diffusion layer, loading an oxygen-coordinated cobalt single-atom catalyst, and performing constant current electrolysis in a flow electrolysis cell using a working condition simulation electrochemical test method, and the evaluation method includes cumulative Faraday efficiency, catalyst Faraday efficiency and electrode stability.

[0065] According to an embodiment of the present invention, the above test may further include at least one of the following additional technical features:

[0066] According to an embodiment of the present invention, the electrode area is 1 cm 2 , control the current density to 50~100mA / cm 2 .

[0067] According to an embodiment of the present invention, the operating condition simulation electrochemical testing method includes the operating condition simulation including start-stop and fluctuating operating conditions.

[0068] According to an embodiment of the present invention, the start-stop condition is to stop intermittently during the constant current electrolysis process, and then resume the constant current electrolysis, and the current density is 50-100 mA / cm 2 The start-stop interval is 0.5 to 20 hours per time.

[0069] According to an embodiment of the present invention, the current density is 50-80 mA / cm 2 , Faraday efficiency ≥ 90%, start-stop interval is 0.5~10h / time.

[0070] According to an embodiment of the present invention, the fluctuating working condition is fluctuating electrolysis within the test current range of 10-20% to 120-150%, and the fluctuation frequency is 0.1-2h / time; preferably, the test current range is 20% to 120%, and the fluctuation frequency is 0.5-1h / time.

[0071] According to an embodiment of the present invention, the cumulative Faraday efficiency is a Faraday test after a simulated operating condition test is completed, and the catalyst Faraday efficiency is a Faraday test of a catalyst constant coulomb test after the test is completed or during an interval.

[0072] According to an embodiment of the present invention, the present invention provides a method for preparing an oxygen-coordinated cobalt single-atom catalyst. According to an embodiment of the present invention, the method comprises: dissolving a cobalt salt and a zinc salt into a mixed solution of N,N-dimethylformamide, water and ethanol, namely solution A, dissolving terephthalic acid into the same mixed solution to obtain solution B; clarifying solution A and solution B, mixing, dripping triethylamine thereto, uniformly dispersing them by ultrasonic aging, centrifuging to separate the metal organic framework material containing oxygen coordination; washing and drying the metal organic framework material to obtain a precursor; carbonizing the dried precursor at high temperature under the protection of an inert atmosphere to remove zinc and obtain a powder catalyst; heating the powder catalyst to reflux in an acidic solution to remove excess cobalt particles, and finally obtaining an oxygen-coordinated cobalt single-atom catalyst. The catalyst prepared by the present invention is applied to the preparation of hydrogen peroxide by electrocatalytic oxygen reduction. In the rotating ring disk test, the hydrogen peroxide selectivity is ≥90% in the potential range of 0.2 to 0.5V vs.RHE. Using carbon paper as the gas diffusion layer and loading oxygen-coordinated cobalt single-atom catalyst, constant current electrolysis was carried out in a flow electrolysis cell to simulate start-stop and fluctuating electrolysis conditions. The evaluation methods included cumulative Faraday efficiency, catalyst Faraday efficiency and electrode stability; cumulative Faraday efficiency ≥90%@5h, catalyst Faraday efficiency ≥90%, electrode stability ≥200h, and catalyst Faraday efficiency decay ≤20%.

[0073] According to an embodiment of the present invention, the present invention has at least one of the following beneficial effects:

[0074] (1) The present invention uses an oxygen-rich metal organic framework to anchor the cobalt metal center and form Co-O-C after carbonization. In this oxygen-coordinated cobalt single-atom catalyst, the oxygen coordination structure can adjust the electronic structure of the central metal cobalt to promote the transfer of active sites, provide the best intermediate *OOH adsorption energy, and thus improve the 2e - Selectivity of ORR.

[0075] (2) The oxygen-coordinated cobalt single-atom catalyst provided by the present invention contains trace amounts of cobalt single atoms, which significantly improves activity and stability compared to pure carbon-based catalysts while reducing the risk of metal dissolution. It can effectively solve the current problems of poor catalyst stability and low efficiency under acidic conditions and is suitable for application scenarios with high purity requirements.

[0076] (3) The catalyst of the present invention is used in the application of electrocatalytic oxygen reduction to prepare hydrogen peroxide, and constant current electrolysis is performed to simulate start-stop and fluctuating electrolysis conditions. The flexibility and adaptability of the catalyst / system are evaluated by cumulative Faraday efficiency, catalyst Faraday efficiency and electrode stability, providing theoretical and technical support for the coupling of green energy such as photovoltaic systems with electrocatalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0078] Figure 1 This is the structural diagram of the metal organic framework material precursor;

[0079] Figure 2 This is a spherical aberration-corrected high-angle annular dark field scanning transmission microscope (AC-HAADF-STEM) photograph of the oxygen-coordinated cobalt single-atom catalyst prepared in Example 1;

[0080] Figure 3 This is a curve chart of the fluctuating operating condition simulation test method of Example 7. DETAILED DESCRIPTION

[0081] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0082] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0083] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0084] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0085] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0086] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0087] Embodiment 1:

[0088] Preparation of oxygen-coordinated cobalt single-atom catalyst: cobalt salt and zinc salt are dissolved in a mixed solution of N,N-dimethylformamide, water and ethanol, i.e., solution A, and terephthalic acid is dissolved in the same mixed solution to obtain solution B, wherein the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:1:0.01; clarified solution A and solution B are mixed, triethylamine is added dropwise thereto, and after being uniformly dispersed by ultrasonic aging for 8 hours, oxygen-coordinated metal organic framework materials are separated by centrifugation; the metal organic framework material is washed and dried at 80°C to obtain a precursor; the dried precursor is carbonized at high temperature under the protection of an inert atmosphere, with a heating rate of 2°C / min, a carbonization temperature of 950°C, and a carbonization time of 3 hours to obtain a powder catalyst; the powder catalyst is heated to reflux at 80°C for 2 hours in 1 mol / L HCl to remove excess cobalt particles, and after washing and drying, an oxygen-coordinated cobalt single-atom catalyst is obtained. In the rotating ring disk test, the hydrogen peroxide selectivity was ≥90% in the potential range of 0.1-0.5 V vs. RHE.

[0089] Embodiment 2:

[0090] Preparation of oxygen-coordinated cobalt single-atom catalyst: cobalt salt and zinc salt are dissolved in a mixed solution of N,N-dimethylformamide, water and ethanol, i.e., solution A; terephthalic acid is dissolved in the same mixed solution to obtain solution B, wherein the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:1:0.1; clarified solution A and solution B are mixed, triethylamine is added dropwise thereto, and after being uniformly dispersed by ultrasonic aging for 4 hours, oxygen-coordinated metal organic framework materials are separated by centrifugation; the metal organic framework material is washed and dried at 80°C to obtain a precursor; the dried precursor is carbonized at high temperature under the protection of an inert atmosphere, with a heating rate of 2°C / min, a carbonization temperature of 800°C, and a carbonization time of 3 hours to obtain a powder catalyst; the powder catalyst is heated to reflux at 80°C for 2 hours in 1 mol / L HCl to remove excess cobalt particles, and after washing and drying, an oxygen-coordinated cobalt single-atom catalyst is obtained. In the rotating ring disk test, the hydrogen peroxide selectivity was ≥90% in the potential range of 0.2-0.5 V vs. RHE.

[0091] Embodiment 3:

[0092] Preparation of oxygen-coordinated cobalt single-atom catalyst: cobalt salt and zinc salt are dissolved in a mixed solution of N,N-dimethylformamide, water and ethanol, i.e., solution A; terephthalic acid is dissolved in the same mixed solution to obtain solution B, wherein the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:1:0.5; clarified solution A and solution B are mixed, triethylamine is added dropwise thereto, and after being uniformly dispersed by ultrasonic aging for 1 hour, oxygen-coordinated metal organic framework materials are separated by centrifugation; the metal organic framework material is washed and dried at 80°C to obtain a precursor; the dried precursor is carbonized at high temperature under the protection of an inert atmosphere, with a heating rate of 2°C / min, a carbonization temperature of 950°C, and a carbonization time of 3 hours to obtain a powder catalyst; the powder catalyst is heated to reflux at 80°C in 1 mol / L HCl for 12 hours to remove excess cobalt particles, and after washing and drying, an oxygen-coordinated cobalt single-atom catalyst is obtained. In the rotating ring disk test, the hydrogen peroxide selectivity was ≥85% in the potential range of 0.1-0.6 V vs. RHE.

[0093] Embodiment 4:

[0094] Start-stop condition simulation test: The oxygen-coordinated cobalt single-atom catalyst prepared by the present invention is used for electrocatalytic oxygen reduction to produce hydrogen peroxide. Carbon paper is used as the gas diffusion layer and loaded with the oxygen-coordinated cobalt single-atom catalyst. The electrode area is 1 cm 2 , the current density is controlled to be 10mA / cm 2, constant current electrolysis in a flow electrolytic cell, start-stop interval of 1h / time, start-stop 20h. The system cumulative Faraday efficiency ≥94%@1h, catalyst Faraday efficiency ≥95%. Repeat 50 times, electrode stability ≥100h, catalyst Faraday efficiency decay ≤10%.

[0095] Embodiment 5:

[0096] Start-stop condition simulation test: The oxygen-coordinated cobalt single-atom catalyst prepared by the present invention is used for electrocatalytic oxygen reduction to produce hydrogen peroxide. Carbon paper is used as the gas diffusion layer and loaded with the oxygen-coordinated cobalt single-atom catalyst. The electrode area is 1 cm 2 , the current density is controlled to be 50mA / cm 2 , constant current electrolysis in a flow electrolytic cell, start-stop interval of 10h / time, start-stop 20h. The system cumulative Faraday efficiency ≥90% @1h, catalyst Faraday efficiency ≥90%. Electrode stability ≥200h, catalyst Faraday efficiency decay ≤20%.

[0097] Embodiment 6:

[0098] Fluctuation condition simulation test: The oxygen-coordinated cobalt single-atom catalyst prepared by the present invention is applied to the electrocatalytic reduction of oxygen to produce hydrogen peroxide. Carbon paper is used as the gas diffusion layer, and the oxygen-coordinated cobalt single-atom catalyst is loaded. The electrode area is 1 cm 2 , control the constant current density to 20mA / cm 2 , electrolysis was performed in a flow electrolysis cell with a fluctuation range of 10% to 150%, a fluctuation frequency of 0.5h / time, and 10 fluctuations. The cumulative Faraday efficiency of the system was ≥94%@10h, and the Faraday efficiency of the catalyst was ≥95%. Repeated 10 times, the electrode stability was ≥100h, and the Faraday efficiency decay of the catalyst was ≤5%.

[0099] Embodiment 7:

[0100] Fluctuation condition simulation test: The oxygen-coordinated cobalt single-atom catalyst prepared by the present invention is applied to the electrocatalytic reduction of oxygen to produce hydrogen peroxide. Carbon paper is used as the gas diffusion layer, and the oxygen-coordinated cobalt single-atom catalyst is loaded. The electrode area is 1 cm 2 , control the constant current density to 50mA / cm 2 , electrolysis was performed in a flow electrolytic cell with a fluctuation range of 20% to 120%, a fluctuation frequency of 1h / time, and 10 fluctuations. The cumulative Faraday efficiency of the system was ≥94%@20h, and the Faraday efficiency of the catalyst was ≥80%. Repeated 10 times, the electrode stability was ≥200h, and the Faraday efficiency decay of the catalyst was ≤10%.

[0101] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0102] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An oxygen-coordinated cobalt single-atom catalyst, characterized in that: The oxygen-coordinated cobalt single-atom catalyst is composed of a porous carbon skeleton, cobalt single atoms and oxygen atoms, and the specific surface area of ​​the porous carbon skeleton is 100 to 3000 m 2 / g, the mass content of the cobalt single atom is 0.01% to 10%, and the mass content of the oxygen atom is 1% to 15%.

2. A method for preparing an oxygen-coordinated cobalt single-atom catalyst, characterized in that: include: 1) dissolving a cobalt salt and a zinc salt in an organic solution to obtain a solution A; 2) dissolving terephthalic acid in an organic solution to obtain solution B; 3) mixing the solution A, the solution B and triethylamine to obtain a metal organic framework material containing oxygen coordination; 4) washing and drying the oxygen-coordinated metal organic framework material to obtain a precursor; 5) subjecting the precursor to a carbonization reaction to obtain a powder catalyst; 6) The powder catalyst is subjected to heating reflux treatment to obtain an oxygen-coordinated cobalt single-atom catalyst.

3. The method according to claim 2, characterized in that The organic solvent in step 1) and step 2) is the same; Optionally, the organic solution is selected from one or more of N,N-dimethylformamide, water, ethanol, and methanol; Optionally, the molar ratio of terephthalic acid, zinc salt and cobalt salt is 1:(0.1-1):(0.01-0.5); Optionally, the cobalt salt and the zinc salt are one or both of nitrate and chloride salts.

4. The method according to claim 2, characterized in that: The mixing treatment is carried out by ultrasonic aging; Optionally, the ultrasonic aging time is 1 to 10 hours; Optionally, the temperature of the ultrasonic aging is 20-45°C.

5. The method according to claim 2, characterized in that: The drying temperature is not less than 70°C; Optionally, the drying process is performed under a vacuum environment; Optionally, the drying time is 8 to 12 hours.

6. The method according to claim 2, characterized in that The carbonization treatment is carried out under an argon atmosphere; Optionally, the heating rate of the carbonization treatment is 2 to 5°C / min; Optionally, the temperature of the carbonization treatment is 800-1000°C; Optionally, the carbonization treatment time is 1 to 5 hours.

7. The method according to claim 2, characterized in that The heating reflux treatment is carried out in an acidic solution; Optionally, the concentration of the acidic solution is 0.1 to 3 mol / L; Optionally, the temperature of the heating reflux treatment is 40 to 100° C.; Optionally, the heating reflux treatment time is 2 to 24 hours.

8. Use of the oxygen-coordinated cobalt single-atom catalyst according to claim 1 or the oxygen-coordinated cobalt single-atom catalyst prepared according to the method according to any one of claims 2 to 7 in the preparation of hydrogen peroxide by electrocatalytic oxygen reduction.

9. The use according to claim 8, characterized in that: The electrocatalytic oxygen reduction to prepare hydrogen peroxide is carried out in an acidic medium; Optionally, the acidic medium is one of perchloric acid, sulfuric acid or hydrochloric acid; Optionally, the concentration of the acidic medium is 0.01 to 1 mol / L.

10. The use according to claim 8, characterized in that: The electrocatalytic oxygen reduction to prepare hydrogen peroxide is carried out in a flow electrolytic cell; Optionally, the flow electrolysis cell utilizes one of constant current electrolysis, constant voltage electrolysis or new energy simulated working condition electrolysis; Optionally, the simulated operating condition in the application is one or more of start-stop and fluctuation operating conditions; Optionally, the current density in the simulated working condition is 10 to 500 mA / cm 2 The start-stop interval is 0.01 to 20 h / time; the fluctuating operating condition is to perform alternating electrolysis at 5 to 20% and 120 to 150% of the rated current density, and the fluctuation frequency is 0.01 to 20 h / time.

Citation Information

Patent Citations

  • Catalyst-loaded carbon fiber cloth and preparation method and application thereof

    CN113117679A

  • Ni-N and Co-N loaded double active site doped hollow carbon sphere catalyst as well as preparation method and application thereof

    CN115020918A

  • Preparation method of double-shell hollow porous carbon nanotube loaded cobalt monatomic catalyst

    CN115845853A

  • Co monatomic catalyst, preparation method thereof and hydrogen peroxide preparation method

    CN116676620A

  • Metal catalyst as well as preparation method and application thereof

    CN116899570A